Applied Hierarchical Cluster Analysis with Average Linkage Algoritm - Astuti, Cindy Cahyaning; Untari, Rahmania Sri (CAUCHY, 2017)
This research was conducted in Sidoarjo District where source of data used from secondary data contained in the book "Kabupaten Sidoarjo Dalam Angka 2016" .In this research the authors chose 12 variables that can represent sub-district characteristics in Sidoarjo. The variable that represents the characteristics of the sub-district consists of four sectors namely geography, education, agriculture and industry. To determine the equitable geographical conditions, education, agriculture and industry each district, it would require an analysis to classify sub-districts based on the sub-district characteristics. Hierarchical cluster analysis is the analytical techniques used to classify or categorize the object of each case into a relatively homogeneous group expressed as a cluster. The results are expected to provide information about dominant sub-district characteristics and non-dominant sub-district characteristics in four sectors based on the results of the cluster is formed.